Evaluación de la contribución de las quemas de biomasa en las concentraciones de Black Carbon en Barranquilla, Atlántico (2023)
The deterioration of air quality resulting from biomass burning is one of the greatest concerns today, due to the emissions of some atmospheric pollutants, among which Black Carbon (BC) stands out, considered a pollutant with a strong contribution to radiative forcing and consequently altering the climate. In this research, BC was monitored environmentally through an AE33 ethalometer, this instrument allowed the determination of concentrations and the identification of the contribution of burning and vehicular traffic, in addition to the Ångström absorption exponent, which is essential for the identification of burning. To relate the percentage contribution of the burns in the city of Barranquilla obtained by the AAE33 vs. those obtained by the modeling, a modeling was used in which the burning points were identified and then fed to the Hysplit trajectory dispersion model for the sampling period from June 1, 2019 to June 30, 2020. The results obtained were an ambient BC concentration of 0.80 ± 0.64 μg/m3, a biomass burning contribution percentage of 17.2% thus obtaining a remaining vehicle traffic contribution of 82.8% and a high correlation in the variables humidity, atmospheric pressure and solar radiation.